Effect of LDL cholesterol, statins and presence of mutations on the prevalence of type 2 diabetes in heterozygous familial hypercholesterolemia - Elisenda Climent (Nature Portfolio, 2017)
Abstract Patients with heterozygous familial hypercholesterolemia (HeFH) have been reported to be less vulnerable to type 2 diabetes mellitus (T2DM), although the mechanism is unknown. The aims of the present study were to assess the effects of low density lipoprotein (LDL) cholesterol concentration and the presence of FH-causing mutations on T2DM prevalence in HeFH. Data were collected from the Dyslipidemia Registry of the Spanish Arteriosclerosis Society. Inclusion criteria were definite or probable HeFH in patients aged ≥18 years. T2DM prevalence in HeFH patients was compared with data of the general population. 1732 patients were included. The prevalence of T2DM was lower in patients with HeFH compared with the general population (5.94% vs 9.44%; OR: 0.606, 95% CI 0.486–0.755, p < 0.001). Risk factors for developing T2DM were male sex, age, body mass index, hypertension, baseline triglyceride levels and years on statin therapy. The prevalence of T2DM in HeFH patients was 40% lower than that observed in the general population. Gene mutations and LDL cholesterol concentrations were not risk factors associated with the prevalence of T2DM in patients with HeFH. The prevalence of T2DM in patients with HeFH was 40% lower than in the general population matched for age and sex.